Long-term effects of cognitive behavioural therapy on the quality of life in adult ADHD - Ravian Wettstein; Valentina Navarro-Ovando; Viktoria Janke; Ron Mathôt; Glenn Dumont (PLOS One, 2026)
This study examined the long-term effects (4–8 years) of Cognitive Behavioural Therapy (CBT), added to pharmacotherapy and psychoeducation (PE), on quality of life (QoL) in adults with Attention-Deficit/Hyperactivity Disorder (ADHD). Although previous findings showed no added QoL benefit of CBT immediately post-treatment, CBT provides skill-building and coping strategies that may yield delayed benefits in terms of ADHD-related functional impairments. We hypothesize that CBT will provide delayed treatment gains and thus results in higher QoL at follow-up or a slower decline in QoL over time. A follow-up study was conducted with 627 adults from a prior cohort that evaluated short-term CBT outcomes. Of these, 159 participants completed a long-term follow-up survey assessing QoL using the Adult ADHD Quality of Life scale (AAQoL). A linear mixed model revealed no significant treatment or treatment-by-time effects for the total AAQoL or its subdomains. However, a significant effect of time was observed across all measures. Post hoc comparisons indicated an increase in QoL from baseline (pooled mean = 44.4; PsyEd: 46.4, PsyEd + CBT: 42.4) to post-treatment (69.3), followed by a decline at follow-up (52.1), which remained above baseline levels. No significant between-group differences were found in the proportion of participants achieving clinically meaningful QoL improvements over time. These findings suggest that this study does not provide evidence for an added long-term QoL benefit of CBT beyond PE and pharmacotherapy, whereas initial treatment was associated with sustained improvement. Continued care beyond initial treatment may help maintain gains in adults with ADHD.